EFEKTIVITAS PENERAPAN MODEL INQUIRY LEARNING DENGAN DISCOVERY LEARNING TERHADAP KEMAMPUAN LITERASI SAINS DI SEKOLAH DASAR - Kristiyani, Rosi Juniartika; Endang Indarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the application of the steps of the Inquiry learning model to scientific literacy abilities, to analyze the application of the steps of the Discovery learning learning model to scientific literacy abilities in elementary schools, and to prove the effectiveness of applying the Inquiry learning model with Discovery learning to scientific literacy abilities in Elementary School. This type of research is quasi-experimental (Quasi Experimental Research) with a pseudo-quasi design. In this study, the researchers divided into experimental classes consisting and control class Data collection techniques through observation and tests to measure IPAS scientific literacy abilities. Based on the results of research and data analysis, it can be concluded that the application of the Discovery learning learning model is more effective in improving scientific literacy skills than Inquiry. This is shown by the results of the t count in the independent sample t-test which was carried out after treatment, it was found that the 2-tailed significance was 0.000, which was less than 0.05 (0.000<0.05), so Ho was rejected and Ha was accepted. In the Discovery Learning model, students work on their own to find solutions to problems and the knowledge that accompanies them will produce truly meaningful knowledge. Apart from that, the Discovery learning model emphasizes active student learning in discovering concepts.